The equation of the exponential function is [tex]y = 3^{-x -5} - 3[/tex]
An exponential equation is represented as:
y = b^x
Where b represents the base.
The base is 3.
So, we have:
[tex]y = 3^x[/tex]
When reflected over the y-axis, we have:
[tex]y = 3^{-x[/tex]
When shifted right by 5 units, we have:
[tex]y = 3^{-x -5[/tex]
Lastly, the function has an asymptote of y=-3
So, we have:
[tex]y = 3^{-x -5} - 3[/tex]
Hence, the equation of the exponential function is [tex]y = 3^{-x -5} - 3[/tex]
Read more about exponential function at
https://brainly.com/question/2456547
#SPJ1